IMPLEMENTATION OF PROJECT-BASED LITERATURE IN STUDENTS' WRITING PERFORMANCE - Irma Manda Negara; Nurul Hidayati; Kristina Laora (Jurnal Ilmiah Spectral, 2023)
This study aims to describe the process and learning activities of implementing PjBL in writing based on literature and students' writing performance after implementing PjBL. The qualitative method is used in this study. Data collection used observation checklists and interviews. Data is analyzed with represented, interpreted meaning, and reflected. The results show that the lecturer has carried out the stages of PjBL activities in accordance with theoretical references, starting from the planning stage to concluding. On the other hand, the results of students' writing performance showed an increase. This increase can be seen in the learning outcomes after implementing PjBL. Then, implementing PjBL helps students determine topics and ideas for them to put into their writing. The collaborative work offered by PjBL is also beneficial for students in writing. Finally, PjBL is recommended to be applied in learning, developing the targeted primary skills and skills included in "success skills."